Uses, benefits and challenges of using rural community telecentres as tools for development: the Case of Vikwa Community Telecentre in Kasungu, Malawi - Kapondera, Sellina Khumbo; Namusanya, Dave Mankhokwe (African journals online, 2016)
This paper examines the uses, benefits and challenges of using telecentres as tools for development in Malawi focusing on one community telecentre: Vikwa Community Telecentre in the Kasungu district of Malawi. Quantitative and qualitative data were gathered using a questionnaire administered to 46 users; interviews with the Telecentre Manager; and observation of the categories of people coming to the telecentres; what they were using and challenges sues and challenges within the telecentre. The findings indicate that the users are improving their skills and knowledge, school performance, finding new friends and saving money. The community uses the telecentre to improve work related skills, keep in touch with friends and families and look for jobs. The negative finding is that telecentre usage is uneven as users are generally poor male youths with little education. Furthermore, the users face a number of challenges when using the telecentre. For the telecentre to have more impact on development, the paper recommends that the Vikwa Telecentre should work on attracting all groups of people in the community, change the internet service provider, buy an electricity generator, acquire more books and computers and train staff in customer care.